Pengembangan Koperasi Syariah untuk Meningkatkan Perekonomian Desa Hegarmanah - Ahmad, Yono Ali; Abdillah, Iqbal; Supriatna, Yana Achmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of sharia cooperatives has become an important strategy in strengthening the economy of rural communities, especially in Hegarmanah Village. This article examines the implementation of sharia cooperatives as a community-based economic solution to overcome financial problems and improve community welfare. This research uses a descriptive method with a quantitative approach to analyze the impact of Islamic cooperatives on the village economy. The results show that sharia cooperatives are able to increase community income through sharia-based financing, micro-enterprise empowerment, and increased community financial literacy. The findings are expected to serve as a basis for the development of Islamic economic policies at the local level.